2012
DOI: 10.1029/2012gl052590
|View full text |Cite
|
Sign up to set email alerts
|

Aviation induced diurnal North Atlantic cirrus cover cycle

Abstract: [1] Aviation induced cirrus (AIC) cover is identified from mean diurnal cycles of cirrus cover and air traffic density in the North Atlantic flight corridor. Traffic data for this region show an aviation "fingerprint" with two maxima during morning eastbound and afternoon westbound traffic. The same aviation fingerprint is found in cirrus cover. Cycle differences between west and east domain parts allow separating between aviation and natural diurnal changes. Cirrus cover is derived from 8 years of Meteosat in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 27 publications
6
57
0
Order By: Relevance
“…We are aware that a part of the development of the contrail cannot be observed from this satellite platform due to a low optical thickness (or con-trast with the background) and to a sub-pixel width. Several case studies for instruments with a spatial resolution similar to SEVIRI (for example Duda et al, 2004, using GOES imagery) have pointed out that this missing time is close to 1 h. This extra hour is consistent with the fact that the average lifetime of the tracked contrails is around 1 h (plus the additional initial period not visible from the satellite platform) and the average width is reached after around 2.5 h. Our findings are also in agreement with Graf et al (2012), who observed maximum cirrus contrail cover over the North Atlantic between 2.1 and 4.1 h after passage of air traffic.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We are aware that a part of the development of the contrail cannot be observed from this satellite platform due to a low optical thickness (or con-trast with the background) and to a sub-pixel width. Several case studies for instruments with a spatial resolution similar to SEVIRI (for example Duda et al, 2004, using GOES imagery) have pointed out that this missing time is close to 1 h. This extra hour is consistent with the fact that the average lifetime of the tracked contrails is around 1 h (plus the additional initial period not visible from the satellite platform) and the average width is reached after around 2.5 h. Our findings are also in agreement with Graf et al (2012), who observed maximum cirrus contrail cover over the North Atlantic between 2.1 and 4.1 h after passage of air traffic.…”
Section: Discussionsupporting
confidence: 81%
“…CDA is based on the fact that contrails are ice clouds that have a linear structure when they form. It has already been used to study linear contrail coverage on several regions of the Earth: central Europe (Meyer et al, 2002), North America , eastern North Pacific , southern and eastern Asia (Meyer et al, 2007) and the North Atlantic (Graf et al, 2012). A modified version of the algorithm has recently been used by Duda et al (2013); Bedka et al (2013) and Spangenberg et al (2013) to estimate several linear contrail properties in the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anomalies have 0 mean values. Air traffic density in the SAR is practically 0, while traffic in the NAR shows a systematic double-wave diurnal cycle (Graf et al, 2012). Anomalies of cirrus cloud cover and OLR differences between NAR and SAR from MSG show similar patterns with a 2-4 h delay.…”
Section: Comparison Of Contrail Properties With Observations From Spacementioning
confidence: 63%
“…2a, c). Graf et al (2012) reported that a strong diurnal cycle could be identified in aviation induced cirrus cover over the North Atlantic flight corridor with two daily peaks at 06:00 and 18:00 UTC that correlate well with air traffic. Over the eastern US and central Europe, the ice mass and forcing of linear contrails also exhibit very similar behavior as in the global average.…”
Section: Radiative Forcing Of Linear Contrailsmentioning
confidence: 94%